2022
DOI: 10.31080/asms.2022.06.1310
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin, IL-18 and IL-1 Beta as Biomarkers of Metabolic Syndrome in Egyptian Obese Children

Abstract: Background and Objectives: Metabolic syndrome (MetS), one of the most serious global health issues, is considered chronic inflammatory states. Chemerin, Il-18 and Il-1 beta adipocytokines, plays an important role in linking Met S and inflammation. Few studies are conducted in Egypt to disclose the role of chemerin, Il-18 and Il-1 beta as combined biomarkers to increase its diagnostic accuracy. So the aim of our study was to evaluate the role of serum chemerin Il-18 and Il-1 beta as combined biomarkers for earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Gad et al. ( 78 ) revealed higher chemerin serum levels in obese children with metabolic syndrome. In his study chemerin positively correlated with fasting blood glucose and negatively with HDL-C. Other studies confirmed positive relationship between chemerin and insulin and HOMA-IR ( 25 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gad et al. ( 78 ) revealed higher chemerin serum levels in obese children with metabolic syndrome. In his study chemerin positively correlated with fasting blood glucose and negatively with HDL-C. Other studies confirmed positive relationship between chemerin and insulin and HOMA-IR ( 25 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…It's a long-term inflammatory disease. It has been found that the adipocytokines chemerin, IL-8, and IL-1 beta play a crucial role in the link between Met S and inflammation and could serve as useful diagnostic and monitoring markers for the condition (21) .…”
Section: Figure (2)mentioning
confidence: 99%
“…Type II diabetes mellitus is a metabolic disorder characterised by decreased insulin production and elevated blood glucose levels (hyperglycemia). The development of type 2 diabetes mellitus is strongly associated with serum chemerin increases, which are correlated with obesity (21) .…”
Section: Chemerin and Glucose Homeos Tasismentioning
confidence: 99%
See 1 more Smart Citation